2020
DOI: 10.1097/md.0000000000023929
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A∗24:02 associated with lamotrigine-induced cutaneous adverse drug reactions

Abstract: Background: Several studies demonstrated a connection between human leukocyte antigen (HLA)-B∗1502 and lamotrigine (LTG)-induced cutaneous adverse drug reactions (cADRs). The correlation between the HLA-A∗24:02 and LTG-cADRs remains controversial. To examine the associations between HLA-A∗24:02 and LTG-cADRs, we conducted a systematic review and meta-analysis. Methods: We performed a comprehensive search of the literature in several electronic database systems including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A systematic review of 5 studies with drugtolerant and population controls found a statistically significant association between the HLA-A*2402 allele and lamotrigine-induced cutaneous-ADR (cADR) (OR 1.94, 95% CI 1.06-3.54, P=0.03). 9 However, both meta-analyses defined cADRs as inclusive of MPEs, and not solely SCARs. It is noteworthy that only 1 patient in our case series had HLA-B*1502 (data not shown), and 2 patients had HLA-A*2402.…”
mentioning
confidence: 99%
“…A systematic review of 5 studies with drugtolerant and population controls found a statistically significant association between the HLA-A*2402 allele and lamotrigine-induced cutaneous-ADR (cADR) (OR 1.94, 95% CI 1.06-3.54, P=0.03). 9 However, both meta-analyses defined cADRs as inclusive of MPEs, and not solely SCARs. It is noteworthy that only 1 patient in our case series had HLA-B*1502 (data not shown), and 2 patients had HLA-A*2402.…”
mentioning
confidence: 99%